Psoriasis and Psoriatic Arthritis An Integrated Approach - Gordon, Kenneth B.; Gordon, Kenneth B.; Ruderman, Eric M.; Ruderman, Eric M. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
In the past decade it has become increasingly clear that psoriatic disease, both of the skin and joints, can be a significant diagnostic and therapeutic challenge for the physician and a debilitating illness for the patient. At the same time, advances in genetics and immunology have increased our understanding of the pathophysiology of psoriasis and psoriatic arthritis. This text contains a comprehensive discussion by an international group of experts in psoriatic disease of the pathomechanisms, genetics, diagnosis, and treatment of psoriasis and psoriatic arthritis. The information is presented in parallel in order to emphasize the similarities and differences between these two diseases that so commonly occur together. We believe that this approach will make this text an important resource for all practitioners who treat patients with psoriasis and psoriatic arthritis.